1978
DOI: 10.1680/macr.1978.30.104.129
|View full text |Cite
|
Sign up to set email alerts
|

Creep of Concrete in Compression During Drying and Wetting

Abstract: SYNOPSIS The paper describes a study of concrete creep during drying-and-wetting regimes. Damp specimens were loaded at ages of 7 or 140 days and drying began at intervals thereafter. Drying creep was observed; its rate of development was linearly related to that of concurrent shrinkage. The correlation was independent of age at loading and of delay in drying, and only mildly dependent upon stress. For different concretes, drying creep can be closely predicted from water/cement ratio or 28 day strength. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Moreover, a rewetting results in an additional creep strain, opposite to the swelling. This is in agreement with the experimental results reported by Gamble and Parrott 38 and by Day et al 24 The increment of the IDC strain (˜å idc ) p c at time-step˜t p can be written in function of the water content as follows…”
Section: Desiccation Creepsupporting
confidence: 91%
“…Moreover, a rewetting results in an additional creep strain, opposite to the swelling. This is in agreement with the experimental results reported by Gamble and Parrott 38 and by Day et al 24 The increment of the IDC strain (˜å idc ) p c at time-step˜t p can be written in function of the water content as follows…”
Section: Desiccation Creepsupporting
confidence: 91%
“…As already mentioned, the latter is explained by two different mechanisms: (a) the apparent mechanism due to surface microcracking [10] and (b) a true mechanism denoted as stress-induced shrinkage. [11] The experimental results are in line with Gamble and Parrott, [69] Evolution of the total longitudinal strains for unsealed specimens loaded at t 0 = 2, 7, and 28 days, and comparison with test data of Wesche et al [64] FIGURE 12 Relationship between strains associated with drying of specimens, loaded at t 0 = 2, 7, and 28 days, and the respective combined autogenous and drying shrinkage strains for load-free specimens, exposed to drying at t s = 2, 7, and 28 days who found that the development of strain in excess of basic creep is linearly related to that of combined autogenous and drying shrinkage independent of the age at loading. The increasingly larger strain associated with drying of the loaded specimen compared to the respective strain of the load-free specimen for increasing concrete ages at loading, depicted in Figure 12, is also confirmed by the findings of Wittmann and Roelfstra.…”
Section: Tests On Unsealed Loaded Specimenssupporting
confidence: 81%
“…Yet, an increased creep is again observed during swelling ( [28], [30]), which was initially considered paradoxical. However, it is not a paradox according to equation (14).…”
Section: Mechanism Of Drying Creep and Influencing Factorsmentioning
confidence: 99%